Nutrition transition in the Caribbean : a time for action. - HENRY, Fitzroy J. (1996)
Discusses the change in the major type of malnutrition in the Region as the prevalence of marasmus and kwashiorkor fell and obesity emerged as a major nutritional problem. Notes that countries with high prevalence of obesity also report high mortality due to chronic diseases such as diabetes, high blood pressure, coronary heart diseases, stroke and cancer, and that the focus of health and nutrition workers must shift towards obesity and these rapidly increasing chronic diseases - all of which can be controlled by dietary intervention. Advises that the development and implementation of food and nutrition policies requires the participation of government sectors involved in health, education, agriculture, and planning among others, all of them with support from the highest levels of decision-making.